Pengaruh Kompensasi, Kepuasan Kerja, dan Stress Kerja Terhadap Prestasi Kerja Pegawai RSUD Suradadi Kabupaten Tegal - Erianto, Wahyu; Mahanani, Estu (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This study aims to determine the effect of compensation, work satisfaction and work stress on work at RSUD SURADADI Kab. Tegal. In this study, primary data and secondary data were used. This study uses quantitative methods, using a questionnaire technique for data collection with a sample of 58 respondents, consisting of employees of RSUD SURADADI Kab. Tegal. The data analysis used begins with a data quality test consisting of a data validity test and a data reliability test, then continued with descriptive statistics, a classical assumption test consisting of a regression normality test, a multicollinearity test, and a heteroscedasticity test. Hypothesis testing using a significant partial and simultaneous regression test, the coefficient of determination using the SPSS version 25.0 for windows program. Based on the results of the study, the analysis of the coefficient of determination showed that the variables of Compensation, Work Satisfaction, Job Stress Affecting Work Achievement was 77.2%. In addition, it was found that the compensation and activity variables partially have a significant relationship to Work Achievement, while the work stress variable does not have a significant relationship to Work Achievement. In addition, the variables of compensation, work satisfaction, and work stress simultaneously have a significant effect on work Achievement.